Ø¨Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ ÙÙŠ Ù…Ø§Ø¯Ù‘Ø© Ø§Ù„Ù†Ù‘ØÙˆ ÙˆØ§Ù„ØµÙ‘Ø±Ù iSpring Suite ÙØ¹Ø§Ù„ÙŠÙ‘Ø© Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªÙ‘Ø¹Ù„ÙŠÙ…ÙŠØ© - Fadilah, Yayang Wiwik; Sulaikho, Siti (Hijai - Journal on Arabic Language and Literature, 2022)
Â  ABSTRACT The research aims to determine the effectiveness of learning media iSpring Suite android bassed in Nahwu Shorof lesson to increase studentâ€™s learning outcomes of VII (Female) class MTsN 2 Rejoso. The research method uses Research and Development (RnD) of 4D Thiagarajan. The research instrument uses observation, interview, and questionnares. The analysis data of pretest posttest uses a avarage value and Wilcoxon Test meanwhile questionnares uses a Likert scale. The questionnares percentage results from Nahwu Shorof learning with the teacher was 52,27% is categorized enough, meanwhile the interestsity for iSpring Suite learning media was 91,35% is categorized very good. The posttest average value 85,90 has better from pretest that has 44,49, Wilcoxon Test of pretest and post test is 0,000<0,05 indicates that the hypothesis is accepted. Bassed on the research results it can be said that the learning media iSpring Suite android bassed to increase studentâ€™s learning outcomes was effectived. Â  Â  ABSTRAK Penelitian bertujuan mengetahui efektivitas media pembelajaran iSpring Suite berbasis android pada mata pelajaran Nahwu Shorof untuk meningkatkan hasil belajar siswi kelas VII (Putri) MTsN 2 Rejoso. Metode penelitian menggunakan Research and Development (RnD) jenis 4D Thiagarajan. Instrumen penelitian memakai observasi, wawancara, dan angket. Data penelitian berupa data pretest posttest dianalisis menggunakan nilai rata-rata dan Uji Wilcoxon sedangkan angket dianalisis menggunakan skala Likert. Hasil persentase angket mencakup efektivitas pembelajaran Nahwu Shorof bersama guru sebesar 52,27% masuk kategori cukup, sementara minat terhadap media pembelajaran iSpring Suite sebesar 91,35% masuk kategori sangat baik. Rata-rata posttest 85,90 menunjukkan lebih baik daripada pretest yang hanya sebesar 44,49, Uji Wilcoxon pada pretest posttest mendapatkan hasil 0,000<0,05 menujukkan bahwa hipotesis diterima. Sehingga dapat dikatakan bahwa media pembelajaran iSpring Suite berbasis android efektif untuk meningkatkan hasil belajar. Â  Ù…Ù„Ø®Ù‘Øµ Ø§Ù„Ø¨ØØ« Ù‡Ø¯Ù Ø§Ù„Ø¨ØØ« Ù„ØªØ¹Ø±ÙŠÙ ÙØ¹Ø§Ù„ÙŠØ© Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© iSpring SuiteÂ  Ø¹Ù„Ù‰ Ø£Ø³Ø§Ø³ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ ÙÙŠ Ù…Ø§Ø¯Ù‘Ø© Ø§Ù„Ù†ØÙˆ ÙˆØ§Ù„ØµØ±Ù Ù„Ø§Ø±ØªÙØ§Ø¹ Ø¥Ù†Ø¬Ø§Ø² Ø§Ù„ØªØ¹Ù„Ù… Ù„Ù„ØªÙ„Ù…ÙŠØ°Ø§Øª ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø£ÙˆÙ„ Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ù¢ Ø±Ø¬ÙˆØ³Ùˆ. ÙˆØ§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« ÙˆØ§Ù„ØªØ·ÙˆÙŠØ± (Research and Development)Â  ÙÙŠ 4Ø¯ ØªÙŠØ§ØºØ±Ø¬Ø§Ù†. Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ø¨ØØ« Ù…Ù„Ø§ØØ¸Ø© ÙˆÙ…Ù‚Ø§Ø¨Ù„Ø© ÙˆØ§Ø³ØªÙØªØ§Ø¡. ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù†Â  ÙˆØ§Ù„Ø¥Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠÙ‘ (pretest)Â  ÙˆØ§Ù„Ø¥Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠÙ‘ (posttest) Â Ø¨Ù‚Ø¯Ø± Ø§Ù„Ù…ØªÙˆØ³Ø· Ùˆ Wilcoxon Test Ùˆ Ø§Ù„Ø§Ø³ØªÙØªØ§Ø¡ Ø¨Ù…Ù‚ÙŠØ§Ø³ Ù„ÙŠÙƒØ± (Likert). Â Ø£Ø¸Ù‡Ø±Øª Ø§Ù„Ù†Ø³Ø¨Ø© Ø§Ù„Ù…Ø«ÙˆÙŠØ© ÙÙŠ Ø§Ø³ØªÙØªØ§Ø¡ Ù„ÙØ¹Ø§Ù„ÙŠØ© Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù†ØÙˆ ÙˆØ§Ù„ØµØ±Ù Ù…Ø¹ Ø§Ù„Ù…Ø¯Ø±Ø³ 52,27% Ø¯Ù„Ù‘Øª Ø¹Ù„Ù‰ Ø§Ù„ÙƒÙØ§ÙŠØ© Ø¨ÙŠÙ†Ù…Ø§ Ø§Ù„Ø§ØØªÙŠØ§Ø¬Ø© Ø¹Ù„Ù‰ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© iSpring Suite 91,35% Ø¯Ù„Øª Ø¹Ù„Ù‰ Ø¬ÙŠØ¯ Ø¬Ø¯Ø§. ÙˆØ§Ù„Ù‚Ø¯Ø± Ø§Ù„Ù…ØªÙˆØ³Ø· ÙÙŠ Ø§Ù„Ø¥Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠÙ‘ (posttest) 85,90 Ø£ØØ³Ù† Ù…Ù† Ø§Ù„Ø¥Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠÙ‘ (pretest) 44,49 Ùˆ WilcoxonTest ÙŠØ¹Ù†ÙŠ 0,000<0,05 Ø£Ø¸Ù‡Ø±Øª Ø§Ù„ÙØ±Ø¶ÙŠØ© Ù…Ù‚Ø¨ÙˆÙ„Ø©. ÙˆÙ‚ÙŠÙ„ Ø£Ù†Ù‘ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© iSpring SuiteÂ  Ø¹Ù„Ù‰ Ø£Ø³Ø§Ø³ Ø£Ù†Ø¯Ø±ÙˆÙŠØ¯ ÙØ¹Ø§Ù„ÙŠØ© Ù„Ø§Ø±ØªÙØ§Ø¹ Ø¥Ù†Ø¬Ø§Ø² Ø§Ù„ØªØ¹Ù„Ù….Â 